Lightweight high-strength heat-resistant stab-resistant fiber composite material and preparation method thereof
By depositing pyel coating on the surface of UHMWPE fibers and introducing MOF nano -slices and functional components, UHMWPE materials have been solved in the lack of spines resistance, and fibrous composite materials for light, high -strength, heat -resistant, and thorns are realized.
Patent Information
- Application Number
- CN202411663391.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
AI Technical Summary
Existing ultra-high molecular weight polyethylene (UHMWPE) materials have shortcomings in their stab resistance and are difficult to compound with other materials to improve stab resistance.
By painting high -activated polypyle (PPY) coating on the surface of UHMWPE fiber, and introducing a mixture of metal organic skeleton (MOF) nanos and functional components on the fiber surface to achieve the functionalization and high performance of the material.
It significantly improves the resistance, heat resistance and flexibility of fibrous composite materials, and forms a fibrous composite material of light, high -strength, heat -resistant, and anti -spy.
Smart Images

Figure CN119371694A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber composite materials, and in particular to a lightweight, high-strength, heat-resistant and stab-proof fiber composite material and a preparation method thereof. Background Art
[0002] At present, ultra-high molecular weight polyethylene (UHMWPE) is one of the main materials for modern high-performance lightweight protective equipment. Although it has excellent ballistic performance, its stab resistance is insufficient and its surface polarity is low, making it difficult to compound with other materials to improve its stab resistance. Although existing studies have attempted to improve its stab resistance by compounding shear thickening fluid, epoxy resin, etc. with UHMWPE fibers, the improvement efficiency is still limited, and there is a lack of more effective fiber modification and composite material construction methods.
[0003] Polypyrrole (Ppy) is a biomimetic polymer formed by the polymerization of pyrrole monomers. It is usually an amorphous black solid and has a wide range of applications, including biology, ion detection, antistatic materials, and as an activating substance to improve the surface properties of materials. Metal organic frameworks (MOFs) are crystalline materials composed of metal ions and organic ligands. Some MOFs show good toughness and plasticity under specific conditions, allowing them to deform to a certain extent without breaking when subjected to external forces, thereby improving puncture resistance. MOF-type nanosheets can be combined with a variety of functional components due to their adjustable structure and function, large specific surface area, high porosity, and abundant active sites and exchangeable coordination sites. In general, MOFs show important potential in the design and development of new puncture-resistant materials, especially in the fields of military industry, transportation, medicine, etc. Summary of the invention
[0004] The purpose of the present invention is to provide a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material and a preparation method thereof in order to solve the above-mentioned problems. The material of the present invention has a series of advantages such as light weight, heat resistance, stab resistance, and flexibility. It is a modern high-performance lightweight protective equipment with broad application prospects.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] A method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material comprises the following steps:
[0007] S1. preparing activated UHMWPE fiber: preparing activated UHMWPE fiber by pretreating ultra-high molecular weight polyethylene fiber;
[0008] S2, preparing modified UHMWPE fiber: immersing the activated UHMWPE fiber obtained in S1 in a solution containing pyrrole or its derivatives at 8-20°C for 4-8h, then dropping FeCl3 solution into the pyrrole solution to promote the polymerization reaction of pyrrole, and after the dropping is completed, treating in an environment of 8-20°C for 8-16h to prepare modified UHMWPE fiber;
[0009] S3, preparing MOF nanosheets: mixing water, salts, a linker, and a regulator evenly, and then synthesizing MOF nanosheets by microwave assistance;
[0010] S4. Preparation of lightweight, high-strength, heat-resistant and puncture-resistant fiber composite materials: The modified UHMWPE fiber obtained in S2 is fully dried, and then a mixture of functional components and MOF nanosheets is introduced to functionalize and improve its performance to obtain a lightweight, high-strength, heat-resistant and puncture-resistant fiber composite material.
[0011] A further solution is that the diameter of the UHMWPE fiber used in step S1 is 8-15 μm, and the thickness of the single-layer UHMWPE fabric is 350-425 μm; the pretreatment method is one or more of chemical activation, heat treatment, ultraviolet irradiation, and radiation treatment.
[0012] A further scheme is that the pyrrole derivative used in step S2 is selected from one or more of pyrrolidine, pyrroline, dimethylpyrrole, pyrrolo[3,4-b]quinoline, polypyrrole, pyrrole-1,2-dicarboxylic acid, and pyrrole-3-carboxylic acid, and the mass ratio of pyrrole or its derivative to deionized water in the solution of pyrrole or its derivative is 0.01-0.03:1, the volume ratio of the pyrrole or its derivative solution to the FeCl3 solution is 1:0.5-1, and the concentration of the FeCl3 solution is 0.2-0.4 g / mL.
[0013] A further solution is that the salt in step S3 is one or more of zinc acetate, cobalt acetate, zinc chloride, cobalt chloride, zinc nitrate, cobalt nitrate, ferric chloride, zirconium chloride, and copper nitrate.
[0014] A further solution is that the linking agent in step S3 is one or more of N,N-dimethylformamide, terphenyl dicarboxylic acid, diethylene glycol butyl ether, and 2-methylimidazole.
[0015] A further solution is that the regulator in step S3 is one or more of terephthalic acid, phthalic acid, benzoic acid, acetic acid, trifluoroacetic acid, trimesic acid, and sodium dodecyl sulfate, and the mass ratio of water, salts, connector, and regulator in the mixed solution is 50-90:1-4:1-3:1.
[0016] A further solution is that the MOF nanosheets in step S3 include at least one of MIL-type MOFs nanosheets, ZIF-8-type MOFs nanosheets, UiO-type MOFs nanosheets, and HKUST-1 nanosheets, and the average thickness of the nanosheets is 1 to 50 nm and the average lateral size is 3 to 20 μm.
[0017] In a further embodiment, the functional component in step S4 is at least one of polyurethane, epoxy resin, polyimide resin and phenolic resin.
[0018] In a further embodiment, the process method for achieving functionalization and high performance of the fiber in step S4 is at least one or more of coating (including brushing, knife coating, spraying, dipping), rolling, casting or hot pressing;
[0019] The light-weight, high-strength, heat-resistant and stab-resistant fiber composite material obtained in step S4 has a single-layer thickness of 390-450 μm, a hardness of 60-75 HV, a heat-resistant temperature of 100-250° C., and a tensile strength of 150-360 MPa.
[0020] Another aspect of the present invention also provides a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material obtained by the above-mentioned preparation method and its use.
[0021] The beneficial effects of the present invention are:
[0022] A lightweight, high-strength, heat-resistant, and puncture-resistant fiber composite material and a preparation method thereof of the present invention deposit a highly active polypyrrole (Ppy) coating on the surface of UHMWPE fibers, utilize its strong adhesion properties, and compound with other materials through intermolecular forces, thereby improving the surface polarity of UHMWPE fibers. Subsequently, a mixture of metal organic framework (MOF) nanosheets and functional components is introduced onto the fiber surface through coating, rolling, casting and other process steps to achieve functionalization and high performance of the material. The prepared fiber composite material exhibits multiple advantages such as light weight, heat resistance, excellent puncture resistance, and high flexibility.
[0023] The Ppy coating not only improves the surface polarity of the UHMWPE fiber, but also increases the surface shear strength, tensile strength and fracture toughness of the material by increasing the friction between the fibers. In addition, the introduction of MOF nanosheets and functional components not only enhances the mechanical properties of the fiber, but also gives the material properties such as light weight and heat resistance, and significantly improves its puncture resistance. Therefore, this lightweight, high-strength, heat-resistant, and puncture-resistant fiber composite material has great application potential in military protection, industrial safety, medical protection and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 The present invention is a flow chart of the preparation method.
[0026] Figure 2 This is a scanning electron microscope image of the MIL-53(Fe) type MOF nanosheet obtained in Example 1 of the present invention.
[0027] Figure 3 This is a scanning electron microscope image of the lightweight, high-strength, heat-resistant and stab-proof fiber composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0029] Example 1
[0030] A lightweight, high-strength, heat-resistant, and stab-resistant fiber composite material and a preparation method thereof, comprising the following steps:
[0031] S11, preparing activated UHMWPE fiber: immersing UHMWPE fiber (diameter of 14 μm, thickness of 400 μm) in a solution containing potassium dichromate, sulfuric acid and distilled water (mass ratio of the three is 7:150:12, treatment time is 1 hour), and obtaining activated UHMWPE fiber after treatment;
[0032] S12, preparation of modified UHMWPE fiber: The activated UHMWPE fiber obtained in S11 was immersed in 500mL of pyrrole solution (the mass ratio of pyrrole monomer to deionized water was 0.0125:1) (treatment temperature 8°C, treatment time 4h), and then 225mL, 0.2g / mL FeCl3 solution was added dropwise to the pyrrole solution to promote the polymerization reaction of pyrrole. After the addition was completed, the mixture was treated in an environment of 8°C for 8h to obtain modified UHMWPE fiber;
[0033] S13, preparation of MOF nanosheets: prepare 500 mL of nanosheet dispersion (deionized water, ferric chloride, N,N-dimethylformamide, terephthalic acid in a mass ratio of 87:3.07:2.62:1), place in a microwave reactor at 170°C for 2 hours and then centrifuge and dry to obtain MIL-53(Fe) type MOF nanosheets (average thickness of 10.1 nm, average lateral size of 12.8 μm);
[0034] S14. Preparation of lightweight, high-strength, heat-resistant and puncture-proof fiber composite materials: The modified UHMWPE fiber obtained in S12 is fully dried at 60°C, and then 0.95g of polyimide resin is mixed with 1g of MIL-53(Fe) type MOF nanosheets obtained in S13 and uniformly rolled (pressure 0.15MPa, speed 10r / min, temperature 60°C) on its surface to achieve functionalization and high performance, thereby obtaining a lightweight, heat-resistant and puncture-proof fiber composite material (thickness 450μm, hardness 75HV, heat resistance temperature 250°C).
[0035] Example 2
[0036] A lightweight, high-strength, heat-resistant, and stab-resistant fiber composite material and a preparation method thereof, comprising the following steps:
[0037] S21, preparing activated UHMWPE fiber: immersing UHMWPE fiber (diameter 14 μm, thickness 400 μm) in 500 mL of a mixed solution of potassium permanganate and nitric acid (mass ratio of potassium permanganate to nitric acid is 1:30, treatment time is 5 min), and obtaining activated UHMWPE fiber after treatment;
[0038] S22, preparation of modified UHMWPE fiber: The activated UHMWPE fiber obtained in S21 was immersed in 500mL of pyrrole solution (the mass ratio of pyrrolidine to deionized water was 0.0112:1) (treatment temperature 8°C, treatment time 4h), and then 225mL, 0.2g / mL FeCl3 solution was added dropwise to the pyrrole solution to promote the polymerization reaction of pyrrole. After the addition was completed, the mixture was treated in an environment of 8°C for 8h to obtain modified UHMWPE fiber;
[0039] S23, preparing MOF nanosheets: preparing 500 mL of nanosheet dispersion (deionized water, zinc chloride, 2-methylimidazole, sodium dodecyl sulfate in a mass ratio of 60:2:1.8:1), placing it in a microwave reactor at 200°C for 2 hours, and then centrifugally drying to obtain ZIF-8 (Zn) type MOF nanosheets (average thickness of 6.8 nm, average lateral size of 10.5 μm);
[0040] S24. Preparation of lightweight, high-strength, heat-resistant and puncture-proof fiber composite materials: The modified UHMWPE fiber obtained in S22 is fully dried at 60°C, and then 0.71g of epoxy resin is mixed with 0.8g of ZIF-8 (Zn) type MOF nanosheets obtained in S23 and evenly sprayed (spraying time 5min) on its surface to achieve functionalization and high performance, thereby obtaining a lightweight, heat-resistant and puncture-proof fiber composite material (thickness 435μm, hardness 70HV, heat resistance temperature 195°C).
[0041] Example 3
[0042] A lightweight, high-strength, heat-resistant, and stab-resistant fiber composite material and a preparation method thereof, comprising the following steps:
[0043] S31, preparing activated UHMWPE fiber: placing UHMWPE fiber (diameter 12 μm, thickness 380 μm) in an oven, treating at 60° C. for 8 h, to obtain activated UHMWPE fiber;
[0044] S32, preparation of modified UHMWPE fiber: The activated UHMWPE fiber obtained in S31 was immersed in 500mL of pyrrole solution (the mass ratio of dimethylpyrrole to deionized water was 0.0150:1) (treatment temperature 8°C, treatment time 4h), and then 225mL, 0.2g / mL FeCl3 solution was added dropwise to the pyrrole solution to promote the polymerization reaction of pyrrole. After the addition was completed, the modified UHMWPE fiber was treated in an environment of 8°C for 8h to obtain;
[0045] S33, preparing MOF nanosheets: preparing 500 mL of nanosheet dispersion (deionized water, zirconium chloride, terphenyl dicarboxylic acid, benzoic acid in a mass ratio of 54:1.56:1.65:1), placing in a microwave reactor at 160°C for 2 hours and then centrifugally drying to obtain UiO-68 (Zr) type MOF nanosheets (average thickness of 6.5 nm, average lateral size of 10.7 μm);
[0046] S34. Preparation of lightweight, high-strength, heat-resistant and puncture-proof fiber composite materials: The modified UHMWPE fiber obtained in S32 is fully dried at 60°C, and then 0.48g of thermoplastic polyurethane is mixed with 0.9g of UiO-68(Zr) type MOF nanosheets obtained in S33 and hot-pressed (temperature 40°C, pressure 2MPa) on its surface to achieve functionalization and high performance, thereby obtaining a lightweight, heat-resistant and puncture-proof fiber composite material (thickness 400μm, hardness 70HV, heat-resistant temperature 170°C).
[0047] Comparative Example 1 (UHMWPE fiber is not pretreated)
[0048] The only difference from Example 1 is that this example does not pretreat the UHMWPE fiber. Specifically, the UHMWPE fiber is directly immersed in the pyrrole solution. Subsequently, a mixture of 0.95 g of polyimide resin and 1 g of MIL-53 (Fe) type MOF nanosheets is uniformly rolled (pressure 1 MPa, temperature 30°C) on its surface to obtain a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material.
[0049] Comparative Example 2 (Functionalization and high performance of modified UHMWPE fiber without using a mixture of functional components and MOF nanosheets)
[0050] The difference from Example 1 is that in this example, the mixture of polyimide resin and MIL-53 (Fe) type MOF nanosheets is not rolled on the surface of the modified UHMWPE fiber. Specifically, the modified UHMWPE fiber is prepared by the same preparation method as in Example 1, and a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material can be obtained after drying.
[0051] Comparative Example 3 (pyrrole solution treatment temperature is 150°C)
[0052] The difference from Example 1 is that in this example, the UHMWPE fiber is immersed in a 150° C. pyrrole solution for activation treatment.
[0053] Comparative Example 4 (preparation of MOF nanosheets without microwave-assisted method)
[0054] The only difference from Example 1 is that this example does not use the microwave-assisted method to prepare MIL-53 (Fe) type MOF nanosheets. Specifically, 500 mL of nanosheet dispersion (deionized water, ferric chloride, N, N-dimethylformamide, terephthalic acid in a mass ratio of 87:3.07:2.62:1) was prepared, and magnetic stirring was performed at room temperature for 2 hours, and then centrifuged and dried to obtain MIL-53 (Fe) type MOF nanosheets (average thickness of 10.1 nm, average lateral size of 12.8 μm).
[0055] Structural characterization and performance testing
[0056] Scanning electron microscope observation: The microstructure of the modified high-performance fibers was observed by field emission scanning electron microscope (model JSM-7900F, JEOL).
[0057] Puncture resistance performance test: The puncture test is carried out using a puncture resistance performance tester (Hongda). The test standard is based on ASTM F1342-05. Each parameter sample is tested 6-8 times, and the results are taken as the average value.
[0058] Mechanical properties test: The obtained lightweight, high-strength, heat-resistant and stab-resistant fiber composite material was cut to obtain tensile specimens, and the mechanical properties of the composite material were tested using a universal testing machine (model 5982, Instron, USA) according to the ASTM D638-2003 plastic tensile properties test standard of the American Society for Testing and Materials. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.
[0059] Table 1. Mass changes of single-layer UHMWPE fiber fabric at various stages of modification (15cm×15cm)
[0060]
[0061] Table 2. Puncture resistance and mechanical properties of fiber composite materials (single layer) obtained in Examples and Comparative Examples
[0062]
[0063] Experimental results: Figure 2 It shows that the microwave-assisted method in Example 1 can successfully prepare MIL-53(Fe) type MOF nanosheets with an average thickness of 10.1 nm and an average lateral size of 12.8 μm. Figure 3 It shows that the appropriate amount of polyimide resin is tightly combined with UHMWPE fibers, and the fibers are bonded to each other, which can not only prevent the nanosheets from falling off, but also improve the puncture resistance. In addition, the MOF nanosheets form a layer of uneven structure on the fiber surface, which increases the surface roughness of the fiber and the friction of external objects on the fiber, thereby increasing the resistance during puncture. At the same time, compared with MOF nanocrystals, MOF nanosheets have a larger specific surface area, which can effectively disperse stress and reduce local pressure when external objects exert pressure on the fiber, avoiding external objects from directly exerting excessive impact force on the fiber, thereby protecting the fiber from being easily punctured.
[0064] Table 1 shows the weight changes of UHMWPE fiber fabrics at various stages of modification. In Examples 1-3, the weight of the fiber modified with pyrrole is increased by up to 5.0% compared with the original UHMWPE fiber. The weight of the fiber functionalized and high-performance UHMWPE fiber using a mixture of functional components and MOF nanosheets is increased by up to about 16.0% compared with the original UHMWPE fiber, indicating that the prepared fiber composite material has the characteristics of light weight. In Comparative Example 3, the weight of the UHMWPE fiber after being immersed in a 150°C pyrrole solution is significantly improved compared with the weight of Example 1. The reason is that when the reaction temperature is increased, the residual Fe 3+ In situ thermal hydrolysis to β-FeOOH (Fe 3++H2O→β-FeOOH) is directly deposited on the surface of the UHMWPE fiber, increasing the mass of the surface deposits. It is obvious from Comparative Example 4 that the quality of the prepared lightweight, high-strength, heat-resistant and stab-resistant fiber composite material is significantly lower than that of Comparative Example 1 without using the microwave-assisted method to prepare MIL-53(Fe) type MOF nanosheets. The main reason is that at room temperature, the reaction progress of the nanosheets is slow and the reaction is not thorough, which leads to a decrease in the overall synthesis quality of the nanosheets. In addition, Examples 1-3 respectively use functional components of polyimide resin, epoxy resin and thermoplastic polyurethane to strengthen UHMWPE fiber fabrics, and the effects are also significantly different.
[0065] Table 2 shows the puncture resistance and mechanical properties of the fiber composite materials (single layer) obtained in the examples and comparative examples. Compared with comparative example 2, which does not use a mixture of functional components and MOF nanosheets to functionalize and improve the performance of the fiber fabric, the puncture resistance of Examples 1-3 is improved. In particular, the maximum puncture force of the fiber composite material (single layer) obtained in Example 1 reaches 220.78N. In addition, the tensile strength and elongation at break also show similar patterns. In comparative example 3, although the increase in temperature is more conducive to the pyrrole polymerization reaction, the UHMWPE fiber fabric may undergo thermal degradation under excessively high temperature conditions, so its puncture resistance is reduced compared to Example 1.
[0066] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations. In addition, the various different embodiments of the present invention can also be combined arbitrarily, as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material, characterized in that: The following steps are involved: S1. preparing activated UHMWPE fiber: preparing activated UHMWPE fiber by pretreating ultra-high molecular weight polyethylene fiber; S2, preparing modified UHMWPE fiber: immersing the activated UHMWPE fiber obtained in S1 in a solution containing pyrrole or its derivatives at 8-20°C for 4-8h, then dropping FeCl3 solution into the pyrrole solution to promote the polymerization reaction of pyrrole, and after the dropping is completed, treating in an environment of 8-20°C for 8-16h to prepare modified UHMWPE fiber; S3, preparing MOF nanosheets: mixing water, salts, a linker, and a regulator evenly, and then synthesizing MOF nanosheets by microwave assistance; S4. Preparation of lightweight, high-strength, heat-resistant and puncture-resistant fiber composite materials: The modified UHMWPE fiber obtained in S2 is fully dried, and then a mixture of functional components and MOF nanosheets is introduced to functionalize and improve its performance to obtain a lightweight, high-strength, heat-resistant and puncture-resistant fiber composite material.
2. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: The diameter of the UHMWPE fiber used in step S1 is 8-15 μm, and the thickness of the single-layer UHMWPE fabric is 350-425 μm; the pretreatment method is one or more of chemical activation, heat treatment, ultraviolet irradiation, and radiation treatment.
3. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: The pyrrole derivative used in step S2 is selected from one or more of pyrrolidine, pyrroline, dimethylpyrrole, pyrrolo[3,4-b]quinoline, polypyrrole, pyrrole-1,2-dicarboxylic acid, and pyrrole-3-carboxylic acid. The mass ratio of pyrrole or its derivative to deionized water in the solution of pyrrole or its derivative is 0.01-0.03:1, the volume ratio of the pyrrole or its derivative solution to the FeCl3 solution is 1:0.5-1, and the concentration of the FeCl3 solution is 0.2-0.4 g / mL.
4. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: The salt in step S3 is one or more of zinc acetate, cobalt acetate, zinc chloride, cobalt chloride, zinc nitrate, cobalt nitrate, ferric chloride, zirconium chloride and copper nitrate.
5. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: In step S3, the linking agent is one or more of N,N-dimethylformamide, terphenyl dicarboxylic acid, diethylene glycol butyl ether, and 2-methylimidazole.
6. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: In step S3, the regulator is one or more of benzoic acid, phthalic acid, acetic acid, trifluoroacetic acid, trimesic acid, and sodium dodecyl sulfate, and the mass ratio of water, salts, connector, and regulator in the mixed solution is 50-90:1-4:1-3:
1.
7. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: The MOF nanosheets in step S3 include at least one of MIL-type MOFs nanosheets, ZIF-8-type MOFs nanosheets, UiO-type MOFs nanosheets, and HKUST-1 nanosheets, and the average thickness of the nanosheets is 1 to 50 nm, and the average lateral size is 3 to 20 μm.
8. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: In the step S4, the functional component is at least one of polyurethane, epoxy resin, polyimide resin and phenolic resin.
9. The method for preparing a lightweight, high-strength, heat-resistant and stab-resistant fiber composite material according to claim 1, characterized in that: The process method for achieving functionalization and high performance of the fiber in step S4 is at least one or more of coating, rolling, casting or hot pressing; The light-weight, high-strength, heat-resistant and stab-resistant fiber composite material obtained in step S4 has a single-layer thickness of 390-450 μm, a hardness of 60-75 HV, a heat-resistant temperature of 100-250° C., and a tensile strength of 150-360 MPa.
10. A lightweight, high-strength, heat-resistant and stab-resistant fiber composite material obtained by the preparation method according to any one of claims 1 to 9 and use thereof.
Citation Information
Patent Citations
Method for modifying ultrahigh molecular weight polyethylene fiber by plasma treatment
CN101532244A
Two-dimensional MOF nanosheet modified fibrous membrane composite material and preparation method thereof
CN115652638A
Microwave-assisted nanometer welding modification method, modified carbon fiber and application of modified carbon fiber
CN117721633A
Ultra-thin ni-fe-MOF nanosheet, preparation method and use thereof
US20210155649A1
Molecularly bonded inherently conductive polymers on substrates and shaped articles thereof
US5691062A
Cited By
Inflatable pasting plate sleeve with anti-collision end face and anti-cutting surface and preparation method of inflatable pasting plate sleeve
CN120003147A